The Mathematical Description of the Electrochemical Function of Cp-Based Electrochemical Sensors, Based on Isomerizing or Exciting Conducting Polymers - Романів, Людмила Вікторівна (Journal of Chemical and Pharmaceutical Research, 2016)
The behavior of CP-based electrochemical sensors, in which the conducting polymer is passing by excited or isomerized state, was analyzed mathematically. The correspondent model was investigated by means of linear stability theory and bifurcation analysis. It was detected that the isomerization (excitation) process may provoke the changes in the structure of double electric layer, capable to cause the oscillatory behavior. The stable steady-state stability depends not only on analyte diffusion and reaction, but also on isomerization (excitation) rate.
Keywords: Conducting polymers; Electrochemical sensors; Isomerization; Excitation; Stable steady-state; Life safety